Problematika Pembelajaran Daring Dalam Aspek Pembelajaran Siswa Sekolah Dasar - Wawan Akbar (Journal on Education, 2023)
The purpose of this research is to analyze the problems of online learning in elementary schools. The results of this study indicate that there are problems when online learning is experienced by teachers, students, and also parents. Problems that arise in the online or distance learning process during the pandemic include minimal supporting facilities, namely students do not have gadgets or unstable signals from teachers and students to carry out online learning, lack of understanding of technology, low enthusiasm for learning, and achievement of learning objectives that cannot be maximized and according to plan